Cushing syndrome in a canine patient with adrenal cortical carcinoma: A case report - Maurenzig, Nelson Damián (2021)
The aim of this work was to highlight the importance of diagnosing the cause of Cushing's syndrome in a 12-year-old male canine patient with adrenal cortical carcinoma, who came to the clinic for presenting clinical signs compatible with Cushing's syndrome. The results of stimulation with synthetic ACTH (Synacthen 0.25 mg®) showed an increase in basal cortisol (10.8 µg/dl) and post-stimulation (28.4 µg/dl). Abdominal ultrasound revealed a rounded and enlarged left adrenal gland (3.3 x 3.4 cm), compatible with adrenal neoplasia. The treatment of choice was adrenalectomy of the left adrenal gland due to a midline abdominal approach and subsequent referral to histopathology for evaluation, which confirmed adrenal cortical carcinoma. Adrenalectomy in these cases increases survival, thus improving the quality of life of the patient.